(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The aim: To reveal new peculiarities of gut microbiota metabolites in CAD patients with or without AF and to detect special connections toward ones with clinical and laboratory features of investigated groups. Materials and methods: 300 patients were investigated. They were divided into 3 groups: control group – 28 patients without CAD and arrhythmias; main group – 149 patients with CAD but without arrhythmias; comparable group – 123 patients with CAD and AF paroxysm. Plasma TMAO, TMA, fecal SCFA levels was determined by gas chromatography with mass electron detection. Results: Metabolomic analysis of the gut microbiota metabolites (plasma TMA, TMAO, fecal SCFA) and clinic-laboratory factors in patients with CAD and AF paroxysm was done in our study. We checked gut microbiota metabolites changes that are common for patients with CAD and AF comparable with CAD patients: increasing of TMA, TMAO plasma levels, fecal valeric acid level (13,88%, 36,52% and 1128,43% respectively, p<0,05) and decreasing total amount of fecal SCFA, USFA, MCFA, butyric, isovaleric, caprylic acids levels (17,09%, 38,16%, 95,54%, 78,75%, 56,29% and 99,21% respectively, p<0,05). Reliable correlations between CAD and AF with TMA, TMAO plasma and fecal SCFA levels were revealed by them and age, BMI, GFR, total cholesterol, TG, LDL, HDL, ApoB levels (|r|>0,3, p<0,05) were revealed that are known risk factors of CAD and AF. Moreover, TMAO, TMA, butyrate, total SCFA, USFA, MCFA levels are closely connected with IL-6 and CRP levels (|r|>0,3, p<0,05). Conclusions: Gut microbiota metabolites (TMA, TMAO, SCFA, MCFA, USFA, butyric acid) are the new promising therapeutic targets for pathogenetic treatment and prevention AF paroxysm in CAD patients.